HERC3 promotes YAP/TAZ stability and tumorigenesis independently of its ubiquitin ligase activity. (4th January 2023) - Yuan, Bo; Liu, Jinquan; Shi, Aiping; Cao, Jin; Yu, Yi; Zhu, Yezhang; Zhang, Chengbin; Qiu, Yifei; Luo, Hongjie; Shi, Jiaxian; Cao, Xiaolei; Xu, Pinglong; et al.
Abstract: YAP/TAZ transcriptional co‐activators play pivotal roles in tumorigenesis. In the Hippo pathway, diverse signals activate the MST‐LATS kinase cascade that leads to YAP/TAZ phosphorylation, and subsequent ubiquitination and proteasomal degradation by SCF β‐TrCP . When the MST‐LATS kinase cascade is inactive, unphosphorylated or dephosphorylated YAP/TAZ translocate into the nucleus to mediate TEAD‐dependent gene transcription. Hippo signaling‐independent YAP/TAZ activation in human malignancies has also been observed, yet the mechanism remains largely elusive. Here, we report that the ubiquitin E3 ligase HERC3 can promote YAP/TAZ activation independently of its enzymatic activity. HERC3 directly binds to β‐TrCP, blocks its interaction with YAP/TAZ, and thus prevents YAP/TAZ ubiquitination and degradation. Expression levels of HERC3 correlate with YAP/TAZ protein levels and expression of YAP/TAZ target genes in breast tumor cells and tissues. Accordingly, knockdown of HERC3 expression ameliorates tumorigenesis of breast cancer cells. Our results establish HERC3 as a critical regulator of the YAP/TAZ stability and a potential therapeutic target for breast cancer. Synopsis: The activity of the Hippo pathway transcriptional co‐activators YAP/TAZ is regulated by several ubiquitin E3 ligases, including the SCF β‐TrCP complex. This study identifies a non‐enzymatic role of the E3 ligase HERC3 in regulation of YAP/TAZ stability in breast cancer. HERC3 can promote YAP/TAZ activation independently of its catalytic activity. HERC3 directly binds to the β‐TrCP substrate recognition subunit to block its recruitment to YAP/TAZ, thus preventing YAP/TAZ ubiquitination and degradation. HERC3 promotes breast tumorigenesis in a YAP/TAZ‐dependent manner. HERC3 expression level correlates with that of YAP/TAZ and their target genes in breast cancer. Abstract : Degradation of two Hippo pathway effectors via the SCF β‐TrCP ubiquitin ligase complex is unexpectedly prevented by another E3 ligase blocking their interaction.